Physicochemical properties and sensory evaluation of Mesona Blumes gum/rice starch mixed gels as fat-substitutes in Chinese Cantonese-style sausage - Feng, T.; Ye, R.; Zhuang, H.; Rong, Z.; Fang, Zhongxiang; Wang, Y.; Gu, Z.; Jin, Z. (Elsevier, 2013)
Effect of Mesona Blumes gum (MBG)/rice starch mixed gels on the fat substitute of Chinese Cantonese-style sausage was investigated in this study, monitored with physicochemical properties and sensory evaluation analyses. Experimental results suggest that there were no significant differences among pH, yield, residual nitrite and TBARS of high-fat (28%), low-fat (18%) and fat-substituted (18%) sausages. The same fat content of low-fat and fat-substituted sausages would aid to compare their physicochemical properties more effectively. In addition, the emulsifying stability and water holding capacity of fat-substituted sausages were better than those of the other groups. During refrigerated storage (4 °C, 3 weeks), fat-substituted sausages reflected similar hardness, chewiness and shear force properties with those of high fat sausages and higher than those of low fat sausages. Furthermore, results of the sensory evaluation indicated that fat-substituted sausages showed superior total acceptability compared with low-fat one after a 2 week refrigerated storage, but was slightly less than that of high-fat one at the same condition. Therefore, MBG/rice starch gels can be effectively used as a fat substitute in Chinese Cantonese-style sausage allowing the manufacture of healthier sausages.